Celebrity ‘Ulama’: Contiguity Religion and Popular Culture - Intan Kumalasari; Darliana Sormin; Muhammad Irsan Barus (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Post-1998 is the spread of spiritualism discourse. The emergence of celebrity ‘ulama’ in Islamic expression of contemporary Indonesian treasury is one example of how popular culture with a set of ideologies taking advantage of the rise of Islam. Television became an agent of a culture to the people with his ability as a link between one culture with another culture. Televisions have unpacked the real with the imaginary. With television all things can be esthetizatied, the sacred and the profane into somersaults. Television media such strength finally gave birth to a new religious authority, called celebrities ‘ulama’. Factors caused by the emergence of celebrity ‘’ulama’ are sociological, which characterized by many people who prefer to watch the celebrity ‘ulama’ than watching Conventional Ulama. Then supported by sophisticated Tecnology Science, the stage, and commodification. This shows that Islam has been negotiating with the market and subsequently published widely in the public sphere as a form of freedom of expression in the new order in which the strength of the potential of Islam to be appreciated by the government. This can be described as a form of commodification of religion in the sense of religious values ​​commercialized for profit.